Short term and long term effects of early language learning - Mihaljević Djigunović, Jelena (2007)
This paper describes findings obtained in comparative longitudinal studies in which four foreign languages (English, French, German and Italian) were introduced at age 7 as part of an early foreign language learning project in Croatia. Data were collected from three generations of young foreign language learners, whose language learning was observed for eight years. Close to 1, 000 learners were involved in the project. Control groups were drawn from learners who started foreign language learning at age 10, the usual starting age at the time. Data were gathered by means of observation, questionnaires, oral interviews and language tests. Results on the following aspects of their language learning process are described: phonological development, morphosyntactic development, speech production, use of learning strategies, use of communication strategies, cognitive and affective learner characteristics. These are discussed from two perspectives: that of the language learning context (foreign vs. second language context) and from the broader second language acquisition perspective.